Neural Correlates of Executed Compared to Imagined Writing and Drawing Movements: A Functional Magnetic Resonance Imaging Study - Baumann, Alexander; Tödt, Inken; Knutzen, Arne; Gless, Carl Alexander; Granert, Oliver; Wolff, Stephan; Marquardt, Christian; Becktepe, Jos S.; Peters, Sönke; Witt, Karsten; Zeuner, Kirsten E. (Frontiers in Human Neuroscience, 2022)
Objective In this study we used functional magnetic resonance imaging (fMRI) to investigate whether motor imagery (MI) of handwriting and circle drawing activates a similar handwriting network as writing and drawing itself. Methods Eighteen healthy right-handed participants wrote the German word “Wellen” and drew continuously circles in a sitting (vertical position) and lying position (horizontal position) to capture kinematic handwriting parameters such as velocity, pressure and regularity of hand movements. Afterward, they performed the same tasks during fMRI in a MI and an executed condition. Results The kinematic analysis revealed a general correlation of handwriting parameters during sitting and lying except of pen pressure during drawing. Writing compared to imagined writing was accompanied by an increased activity of the ipsilateral cerebellum and the contralateral sensorimotor cortex. Executed compared to imagined drawing revealed elevated activity of a fronto–parieto-temporal network. By contrasting writing and drawing directly, executed writing induced an enhanced activation of the left somatosensory and premotor area. The comparison of the MI of these tasks revealed a higher involvement of occipital activation during imagined writing. Conclusion The kinematic results pointed to a high comparability of writing in a vertical and horizontal position. Overall, we observed highly overlapping cortical activity except of a higher involvement of motor control areas during motor execution. The sparse difference between writing and drawing can be explained by highly automatized writing in healthy individuals.